2020
DOI: 10.1590/s1517-707620200002.1071
|View full text |Cite
|
Sign up to set email alerts
|

Anti-adhesion and antibacterial activity of silver nanoparticles and graphene oxide-silver nanoparticle composites

Abstract: The rise of nanotechnology has allowed the development of several inorganic nanoparticles with strong biocidal properties against bacteria, fungi, and viruses. Among them, silver nanoparticles (AgNPs) stand out as one of the most promising antimicrobial nanomaterials. Graphene oxide (GO) is another attractive nanomaterial with antimicrobial properties. Although the antimicrobial effect of AgNPs and GO is known, the development of hybrid materials of GO-AgNPs has considerable interest in various applications si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The outstanding physicochemical characteristics, antimicrobial activity, and biocompatibility of graphene, its derivatives, and nanocomposites make them promising candidates for a large variety of antimicrobial applications, presented in Figure 2. They could be summarized as follows [54][55][56]: support to disperse and stabilize various nanomaterials, such as metals, metal oxides, and polymers with high antibacterial efficiency due to the synergistic effect [55]; antibacterial agents for treatment of multidrug-resistant bacterial infections [34,57]; drug-delivery systems (based on the two-dimensional planar structure, large surface area, chemical and mechanical stability, and good biocompatibility) [34,58]; coatings for medical devices, membranes, and others, due to bread-spectrum antimicrobial activity [59][60][61][62][63][64]; creation of smart material surfaces (graphene materials with controllable wettability) [65]; biosensing and bioimaging (due to the ability to conjugate biomolecules and fluorescent dyes) [54], photothermal therapy (because of the high nearinfrared absorbance of the graphene) and gene therapy [54]; dentistry adhesives and dentin coatings [30,45]; endodontic (irrigants and intracanal medicaments; root canal disinfection) and the regenerative endodontics (support of bioactive molecules and enhancing the scaffold properties [66]; wound dressing and healing [33,40,[67][68][69][70][71]; sewage systems [72]; tissue repair, tissue and organ engineering (made possible by the ability of Gr materials to stimulate the growth of eukaryotic cells and to inhibit the microbial cells attachment and growth; 3D printing of 2D graphene to fabricate 3D structure for bone tissue scaffolds) [54]; antibacterial packaging [73]; water purification membranes…”
Section: Potential Applications Of Graphene Nanomaterialsmentioning
confidence: 99%
“…The outstanding physicochemical characteristics, antimicrobial activity, and biocompatibility of graphene, its derivatives, and nanocomposites make them promising candidates for a large variety of antimicrobial applications, presented in Figure 2. They could be summarized as follows [54][55][56]: support to disperse and stabilize various nanomaterials, such as metals, metal oxides, and polymers with high antibacterial efficiency due to the synergistic effect [55]; antibacterial agents for treatment of multidrug-resistant bacterial infections [34,57]; drug-delivery systems (based on the two-dimensional planar structure, large surface area, chemical and mechanical stability, and good biocompatibility) [34,58]; coatings for medical devices, membranes, and others, due to bread-spectrum antimicrobial activity [59][60][61][62][63][64]; creation of smart material surfaces (graphene materials with controllable wettability) [65]; biosensing and bioimaging (due to the ability to conjugate biomolecules and fluorescent dyes) [54], photothermal therapy (because of the high nearinfrared absorbance of the graphene) and gene therapy [54]; dentistry adhesives and dentin coatings [30,45]; endodontic (irrigants and intracanal medicaments; root canal disinfection) and the regenerative endodontics (support of bioactive molecules and enhancing the scaffold properties [66]; wound dressing and healing [33,40,[67][68][69][70][71]; sewage systems [72]; tissue repair, tissue and organ engineering (made possible by the ability of Gr materials to stimulate the growth of eukaryotic cells and to inhibit the microbial cells attachment and growth; 3D printing of 2D graphene to fabricate 3D structure for bone tissue scaffolds) [54]; antibacterial packaging [73]; water purification membranes…”
Section: Potential Applications Of Graphene Nanomaterialsmentioning
confidence: 99%
“…Table 2 summarizes the MIC values obtained for each sample against the tested microorganisms. It is clearly observed that G-strains are more sensitive to Ag + ions than G+ strains [51][52][53]. The MIC values of GO + Ag for E. coli and P. aeruginosa were only slightly higher than for AgNO 3 , i.e., the antibacterial effect was reduced relatively little (p ˃ 0.05).…”
Section: Antimicrobial Properties Of Fillersmentioning
confidence: 99%
“…It has a larger surface area, high mechanical strength, electric conductivity, and thermal stability, making it photoactive and environmentally beneficial. , Given these remarkable properties, graphene remains the primary choice for researchers to synthesize NMs and nanocomposites. At present, three derivatives of graphene, namely, graphene oxide (GO), reduced graphene oxide (rGO), and graphene quantum dots (GQDs), are regarded as promising fillers in the preparation of nanocomposites that mitigate the antimicrobial resistance observed with biofilm-producing bacterial species, namely, Klebsiella pneumoniae , P. aeruginosa , E. coli , and Bacillus subtilis . …”
Section: Nanomaterials As Antifouling Agentsmentioning
confidence: 99%